Efficacy and Safety of Rimegepant for the Acute Treatment of Migraine: Evidence From Randomized Controlled Trials - Bixi Gao; Yanbo Yang; Zilan Wang; Yue Sun; Zhouqing Chen; Yun Zhu; Zhong Wang (Frontiers Media S.A., 2020)
BackgroundAs one of the novel therapeutic drugs that targets Calcitonin gene-related peptide (CGRP), 75 mg rimegepant has been used for the acute management of migraine, which is one of the most common neurological diseases worldwide. Several clinical trials have been conducted to investigate the efficacy and safety of rimegepant for the acute management of migraine, but no systematic review of existing literature has been performed. We therefore performed a meta-analysis to investigate the efficacy and safety of rimegepant in treatment of patients with migraine.MethodPubmed, Embased, and Cochrane Library were searched from January 2001 to August 2019 for randomized controlled trials (RCTs). Four RCTs with 3,827 patients were finally included in our study.ResultWe pooled 3,827 patients from four RCTs, and the primary endpoints were freedom from pain, most bothersome symptom, and pain relief at 2 hr post dose. We found that 75 mg rimegepant led to significant freedom from pain (P < 0.001), pain relief (P < 0.001), and freedom from the most bothersome symptom (P < 0.001) at 2 hr post dose compared with the placebo. In addition, there was no statistically significant increase in adverse events compared with the placebo.Conclusions75 mg rimegepant had good efficacy and safety for acute treatment of migraine. Further studies are needed to compare the efficacy of rimegepant with traditional drugs for acute management of migraine.